Study on the Effect of Clearance on Eliminating Flexible Impact of Series Geneva Mechanism - Zhao Yong; Huang Chunqiang; Yao Jin; Li Hua (Jixie chuandong)
Using appropriate series geneva mechanism can eliminate the flexible impact in theoretically,but the unavoidable clearances between pin and slot exist in practical engineering application. In order to research the effects of the independent two- stage clearances on eliminating the flexible impact of the whole mechanism,a simulation model of series geneva mechanism containing the clearances is built by using ADAMS software firstly,and the influence mechanism of the clearances affect eliminating the flexible impact of output wheel is conducted. Then the experiment group aiming at finding the influences of different clearances of two stages geneva mechanism on the last geneva wheel is set up. The results illustrate that when the clearances exists,although the output geneva mechanism can eliminate the flexible impact,the impact brought by the clearances has greater influence on it. The peak angular acceleration of the last stage geneva wheel is affected by the first stage pin- slot clearance more greatly than the second one. Finally,a guidance of using series geneva mechanism in actual is brought up: the minimum clearance that ensures the geneva mechanism in normal working condition of the first stage geneva mechanism should be guaranteed with a certain machining accuracy firstly.